A library of 1, 2, 3-triazole-substituted oleanolic acid derivatives as anticancer agents: design, synthesis, and biological evaluation. Issue 5 (5th December 2014) - Wei, Gaofei; Luan, Weijing; Wang, Shuai; Cui, Shanshan; Li, Fengran; Liu, Yongxiang; Liu, Yang; Cheng, Maosheng
Abstract : A series of novel oleanolic acid coupled 1, 2, 3-triazole derivatives have been designed and synthesized by employing a Cu(i ) catalyzed Huisgen 1, 3-dipolar cycloaddition reaction. Abstract : A series of novel oleanolic acid coupled 1, 2, 3-triazole derivatives have been designed and synthesized by employing a Cu(i ) catalyzed Huisgen 1, 3-dipolar cycloaddition reaction. The anti-proliferative evaluation indicated that some compounds exhibited excellent anti-cancer activity against the examined cancer cell lines. Among all derivatives, compound3t possesses the best inhibitory activity against HT1080 cells. A series of pharmacology experiments show that compound3t significantly induced HT1080 cell apoptosis. Therefore, this compound can serve as a promising lead candidate for further study.